Amobilisasi Sel Pediococcus Acidilactici F11 Penghasil Bakteriosin Pada Gel Kalsium Alginat - Saparianti, Ella (Jurnal Teknologi Pertanian, 2001)
Immobilized cell Pediococcus acidilactici F11 that can produce bacteriocin in calciumalginate gel was studied.  This research was conducted to observe the ability of immobilized cell toproduce bacteriocin in TGE broth with initial pH 6,5 in a shaker waterbath at 100 rpm and 37Cfor 24 hours. The cell was immobilized by dropping the mixed of 3% sodium alginate with microbial cells to0,1 M calcium chloride solution.  More than 99% of cell introduced was successfully immobilized. The cell density in beads was in the range of 1,4 x 109 to 1,6 x 1010 cfu /g beads. The ability of immobilized cell and free cell to produce bacteriocin was similar qualitatively.  Theyalso showed similar pH profile during the time of fermentation.Keywords:  immobilized cell, Pediococcus acidilactici F11, bacteriocin, calcium alginate gel